ANALISIS PENINGKATAN KEMAMPUAN MENULIS TEKS NARASI MELALUI MEDIA PUZZLE GAMBAR SERI PADA SISWA KELAS IV SDN TENGGILIS MEJOYO I SURABAYA - Laila Eka Nafilah; M Sukron Djazilan; Pance Mariati; Rudi Umar Susanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the improvement of students' narrative text writing ability after using a series of picture puzzle media in fourth-grade students of SDN Tenggilis Mejoyo I Surabaya. This study uses a quantitative method with One Group Pretest-Posttest Design. The research sample consisted of 27 students. The research instrument was in the form of composing a story that was still random and a narrative text writing test. The pretest results of students who reached the Minimum Completion Criteria (KKM) with a class average score of 46.55 after being given treatment in the form of a series of picture puzzle media, the posttest results increased to 87.03. The results of the N-Gain calculation obtained a value of 0.75 with a high category. This shows that the series of picture puzzle media can improve the narrative text writing ability of fourth-grade students of SDN Tenggilis Mejoyo I Surabaya